Pengaruh Pola Asuh Orang Tua Terhadap Kecerdasan Emosional Anak Kelompok B Di TK Aisyiyah 02 Beruk Jatiyoso Karanganyar Tahun Ajaran 2015/2016 - Taryono, Taryono; , Dra. Surtikanti, S.H., M.Pd; , Junita Dwi Wardhani, SE. M,Ed (2016)
This study aims to determine the effect of parenting authoritarian attitude parents against the emotional intelligence. The study design used in this study is the research thedescriptive quantitative. The approach used in this study is crossecsional. The population in this study is students and and bandung pupils kindergarten Aisyiyah 02 Beruk Jatiyoso Karanganyar group B that numbered in 25 children. Samples used in this study is a total of sampling namely students and parents at kindergarten Aisyiyah 02 Beruk Jatiyoso Karanganyar group B that numbered in 25 children. The result of research shows parenting parents have the influence of positive towards emotional intelligence children, it can be seen from the value of the coefficient of regression on each variable free that was worth positive, such as seen in the equation of regressing linear double the: Y= 6.340+0.824. Furthermore, the results of the analysis of the data obtained the value of the coefficient of determinasi ( R2 ) of 0.676 so it can be taken the conclusion that the emotional intelligence children 67,6 % influenced by variable parenting authoritarian attitude parents and the rest 32,4 % influenced by variable else outside variable research. According to the test hypothesis F show H0 rejected, because Fhitung > Ftabel, namely 47.899 > 3,32 the value of the probability of signifikansi < 0, 05, is 0, 000 so it can be interpreted that there is a significant influence parenting authoritarian attitude parents against the emotional intelligence. The word shouting Key: parenting parents, intelligence emotions, early childhood